Evaluation of early scoring predictors for expedited care in patients with emphysematous pyelonephritis. (February 2022) - Chawla, Arun; Bhaskara, Sunil Pillai; Taori, Ravi; de la Rosette, Jean J.M.C.H; Laguna, Pilar; Pandey, Akhilesh; Mummalaneni, Sitaram; Hegde, Padmaraj; Rao, Shwetapriya; K, Prakashini
Introduction: Emphysematous pyelonephritis (EPN), an acute necrotizing infection of the kidney and surrounding tissues, is associated with considerable mortality. We evaluated how existing critical care scoring systems could predict the need for intensive care unit (ICU) management for these patients. We also analyzed if CT-imaging further enhances these predictive systems. Patients and Methods: A retrospective analysis of 90 consecutive patients diagnosed clinico-radiologically with EPN from January 2011 to September 2020. Five scoring systems were evaluated for their predictive ability for the need for ICU management and mortality risk: National Early Warning Score (NEWS), Modified Early Warning Score (MEWS), 'quick' Sequential Organ Failure Assessment score (qSOFA), Systemic Inflammatory Response Syndrome score (SIRS), and Sequential Organ Failure Assessment score (SOFA). CT images were classified as per Huang & Tseng and evaluated as stand-alone or added to the different predictive models. Receiver operating characteristic (ROC) curves were plotted for each critical care score and CT-Class using logistic regression, to obtain the area under curve (AUC) value for comparison of ICU admission predictability. Patients were analyzed up till discharge. Results: Ninety patients were diagnosed with EPN. Twenty-six patients required ICU management and nine patients died. The best scoring system to predict the need of early ICU management is NEWS (AUC 0.884). CT Class had no independent predictive power, nor did it add significantly to improvement in most of the early warning scoring systems, but rather guided us to the need for radiological, endourological or surgical intervention. Conclusion: In patients with EPN, the NEWS scoring system predicts best the requirement of ICU care. It aids in triage of patients with EPN to appropriate early management and reduce mortality risk.